Challenges and obstacles facing SMEs in the adoption of e-commerce in developing countries; A case of Saudi Arabia - Al-Tayyar, Raed Saud D.; Abdullah, Abdul Rashid; Abd Rahman, Azmawani; Ali, Mass Hareeza (Editorial Universidad de Almería, 2021)
E-commerce has been proposed as the new driver of the growth of any country’s economy. The SME sector plays an important role in contributing to the economy nationally as far as wealth creation by employees is concerned. SMEs in Saudi Arabia represent a significant portion of the productive units in the Saudi economy, and the government policies propose means to improve SME capabilities. Most Saudi Arabian SMEs have had reservations adopting aspects of their enterprises that are electronically delivered. Very few Saudi SMEs, mostly from manufacturing have implemented e-commerce. The results show that some of the hindrances to e-commerce in Saudi include cultural issues, business factors, and technical aspects. Among the facilitators were e-commerce awareness programs, government support for e-commerce adoption, a strong IT infrastructure, and programs for enlightening people. Although studies reveal that government promotions have very little influence on online trade in many countries, this paper has indicated that promotions from the government have boosted e-commerce in Saudi Arabia. This paper studies the challenges and obstacles facing Saudi Arabian SMEs in the adoption of online trade.